Predictors of Quality of Life in Patients Undergoing Hemodialysis for Chronic Kidney Disease (CKD) in Surabaya, Indonesia - Abdul Aziz Alimul Hidayat; Ratna Agustin; Sri Mudji Lestari (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Hemodialysis is the primary therapy for patients with end-stage chronic kidney disease. While it provides essential medical benefits, the procedure also imposes significant physical, psychological, and social challenges, impacting patients’ quality of life. The quality of life of patients with Chronic Kidney Disease (CKD) is influenced by various factors, including individual characteristics such as age, nutritional status, duration of hemodialysis, occupation, gender, and level of education. Advanced age is often associated with a decline in physiological function and an increased risk of complications. Poor nutritional status or malnutrition is linked to higher morbidity and mortality rates. The length of time a patient undergoes hemodialysis may also affect their physical and psychological adaptation, either positively or negatively. This study aims to analyze the predictive factors influencing the quality of life among chronic kidney disease patients undergoing hemodialysis at a private hospital in Surabaya, Indonesia. Methods: This study employed a cross-sectional design involving 160 respondents selected through probability random sampling. Data were collected using the Kidney Disease Quality of Life-Short Form (KDQOL-SF) questionnaire and analyzed using multiple logistic regression to determine significant factors associated with quality of life. Results: The analysis revealed significant associations between age (p=0.001; OR=0.008), duration of hemodialysis (p=0.010; OR=25.916), and nutritional status (p=0.000; OR=0.003) with patients’ quality of life. Patients with poor nutritional status and prolonged hemodialysis duration were at a higher risk of experiencing a decline in quality of life. Conclusion: This study underscores the importance of routine nutritional assessments and targeted monitoring for elderly patients and those with long-term hemodialysis. These strategies are critical to optimizing the quality of life among hemodialysis patients.